DNA–protein crosslink proteases in genome stability - Ruggiano, Annamaria; Ramadan, Kristijan (Communications biology, 2021)
Proteins covalently attached to DNA, also known as DNA–protein crosslinks (DPCs), are common and bulky DNA lesions that interfere with DNA replication, repair, transcription and recombination. Research in the past several years indicates that cells possess dedicated enzymes, known as DPC proteases, which digest the protein component of a DPC. Interestingly, DPC proteases also play a role in proteolysis beside DPC repair, such as in degrading excess histones during DNA replication or controlling DNA replication checkpoints. Here, we discuss the importance of DPC proteases in DNA replication, genome stability and their direct link to human diseases and cancer therapy. DNA–protein crosslink (DPC) proteases digest the protein component of crosslinks that otherwise can cause genomic instability and disease. Ruggiano and Ramadan discuss recent insights into the roles of DPC proteases in the repair of DPCs and beyond.